PROSPECTIVE STRUCTURE OF THE MULTIAGENT SYSTEM OF MANAGEMENT OF THE TRANSPORT COMMUNICATION NETWORK BASED ON CARRIER ETHERNET TECHNOLOGY - Turovsky, Oleksandr; Mishchenko, Andrey; Klobukov, Vitaliy; Kitura, Oleh; Polonsky, Konstantin (Science-based technologies, 2022)
The growing variety of types of transport networks, increasing the diversity of their constituent elements and the number of parameters that characterize the state of these elements causes an expansion of the range of approaches to the management of these networks. The principle of management of any communication network is the interaction of key control units to maintain the readiness of the communication network, the development of management processes and their management during the tasks. Currently, in the development of new principles and methods of managing complex processes have found widespread use of multi-agent technologies - technology development and application of multi-agent systems - complex systems operating with multiple intelligent agents, the process of self-organization of which is reduced to. The paper solves the scientific problem of developing a promising structure of a multi-agent system for managing a transport communication network based on carrier ethernet technology. In order to develop it, the paper proposes the division of CS TCN into three levels, which include the level of organizational management, the level of operational and technical management and technological level. The level of organizational management is designed to ensure the development of decisions on long-term planning management TCN. The level of operational and technical management is designed to provide an array of control mechanisms, control units and ready-made management decisions, which are combined into a plan of measures for the reconfiguration of TCN. The technological level is designed to collect the performance characteristics of TCN and their processing; automatic control of the state of technical means of TCN; the choice of management process, which is determined by the management mechanism defined at the highest level; implementation of the action plan for the reconfiguration of TCN. This distribution created the conditions that allowed the use of multi-agent technologies in the construction of the structure presented in the article.